Identifying Randomized Clinical Trials in Spanish-Language Dermatology Journals (2015)
ABSTRACT: Background: The necessary foundation for good clinical practice lies in knowledge derived from clinical research. Evidence from randomized clinical trials (RCTs) is the pillar on which decisions about therapy are based. Objective: To search exhaustively and rigorously to identify RCTs in dermatology journals published in Spanish. Methods: We located dermatology journals through the following search engines and indexes: PubMed, LILACS, SciELO, Periódica, Latindex, Índice Médico Español, C-17, IBECS, EMBASE, and IMBIOMED. We also sought information through dermatology associations and dermatologists in countries where Spanish was the usual language of publication, and we searched the Internet (Google). Afterwards we searched the journals electronically and manually to identify RCTs in all available volumes and issues, checking from the year publication started through 2012. Results: Of 28 journals identified, we included 21 in the search. We found a total of 144 RCTs published since 1969; 78 (54%) were in Latin American journals and 66 (46%) were in Spanish journals. The most frequent disease contexts for RCTs in Spanish journals were psoriasis, mycoses, and acne vulgaris. In Latin American journals, the most frequent disease contexts were common warts, mycoses, acne vulgaris, and skin ulcers on the lower limbs. Manual searches identified more RCTs than electronic searches. Conclusions: Manual searches found a larger number of RCTs. Relatively fewer RCTs are published in Spanish and Latin American journals than in English-language journals. Internet facilitated access to full texts published by many journals; however, free open access to these texts is still unavailable and a large number of journal issues are still not posted online.